Considerazioni sul continuum natura/tecnica. Il cibo come artefatto ibrido - Onnis, Erica (Bollettino Filosofico, 2023)
Feeding is a fundamental physiological need that falls within the realm of what we consider natural. However, throughout history, human beings have developed and employed several techniques to produce and manipulate food. Therefore, if the classical metaphysical distinction between natural and artefactual entities must be accepted, our food seems to predominantly fall into the latter category. Yet, discussions of artefacts do not typically involve organisms but rather material objects that cannot be found “in nature”. Thus, food may appear as a sui generis artefact. This paper, after an analysis of the relationships holding between food and human beings, suggests that the former, rather than being an unusual artifact is the quintessential artifact, one that seems to reflect better than any other the complex connections between Homo sapiens and its environment. Keywords: Artefacts, Artefactual, Food, Natural, Nature/Technology